The Image of Ancient Lithuania in Latvian Literature of the First Half of the 20th Century - Butkus, Vigmantas (Colloquia, 2023)
The image of ancient Lithuania in Latvian fiction of the first half of the 20th century is usually revealed through works of various genres and uneven artistic quality depicting the ancient history of Latvia and not the history of Lithuania directly. Nearly all such literary pieces are on the tribes that lived in the southern part of Latvia: the Selonians, and especially the Semigallians, whose history is inseparable from Lithuanian history. Unlike the works of 19th-century Latvian authors, 20th-century works no longer depict ancient Lithuanians only in a romantic way, as heroic people that belonged to the same Baltic tribe, but as a powerful and hostile force that threatened the Latvian lands. The image of ancient Lithuania containing the most common historical characteristics prevails; however, it also contains a lot of authorial invention (e.g. the authors write about imaginary “Lithuanian princesses,” or they expand the boundaries of 13th-century Lithuania in an unrealistic way, etc.). The realities of ancient Lithuania, e.g. the historical names and events, are usually presented without any further explanation, which is a sign of an attitude and belief that the reader of the time had sufficient information on the subject.
Keywords: ancient Lithuania; Semigallians; image; historical reality; fiction